THE EFFECT OF SOURSOP LEAF EXTRACT (Annona muricata Linn) ON BCL-2 CONTINOUS CELL T47D ANTI-APOPTOSIS GENE IN BREAST CANCER - Mahendika, Devin; Darnez, Luthfi (Essential: Essence of Scientific Medical Journal, 2023)
Introduction: Breast cancer ranks first in the most cases of malignancy in Indonesia. Phytochemical studies of acetogenin as the main substance of soursop have the potential as a cytotoxic agent and trigger apoptosis of breast cancer cells. Method: This research is a true experimental type using in-vitro studies using continuous cell T47D, the treatment group was given a solution of soursop leaf ethanol extract. The results of this study are seen from the RT-PCR cycle quantification which will be analyzed of the Mann-Whitney Test, and determination of gene expression using the Livak formula. Result: The results showed that the treated T47D cells expressed 1.36 times higher than the control group cells to express the anti-apoptotic protein BCL-2. It’s a significant difference between the treatment and control groups for the expression of the BCL-2 T47D gene , p=0.002 (p<0.005). Discussion: Acetogenin is a strong inhibitor of NADH dehydrogenase which can decrease the production of ATP which can cause death in cancer cells. This inhibition can trigger the activation of the apoptotic pathway and the activation of the BCL-2 gene which can stop the cell cycle which will prevent uncontrolled proliferation. Conclusion: There was a significant difference value of the cycle quantification RT-PCR of the BCL-2 gene in group treatment and control. In addition, soursop leaf extract containing acetogenin was not effective in reducing the expression levels of the anti-apoptotic gene BCL-2 in continuous T47D cells of breast cancer. Keywords: A cetogenin, BCL-2 gene, C ontinuous cell T47D, S oursop leaf extract, RT-PCR .